Migrant top management team and corporate innovation: Evidence from China - Liu Y; Habib A; Huang HJ (John Wiley and Sons Australia, Ltd on behalf of Accounting and Finance Association of Australia and New Zealand, 2025)
This study explores the association between top management teams (TMT) comprised of migrant managers (migrant TMT) and corporate innovation. Using hand-collected data for a sample of Chinese A-share listed firms spanning the period 2008–2020, we find a positive and significant association between a migrant TMT and corporate innovation. Our results remain robust to a set of endogeneity tests, including entropy-balanced regression and instrumental variable regression. We then show that real earnings management and risk-taking are the channels through which the positive relationship between migrant TMTs and corporate innovation manifests itself: migrant TMTs engage less in real earnings management and are more likely to take risks. Finally, we find that the positive relationship between migrant TMTs and corporate innovation is more pronounced in state-owned firms and remains significant in both high- and low-cultural diversity regions, suggesting that the observed effect is not primarily driven by cultural adaptability but reflects a robust migration-driven mechanism. Our findings contribute to the literature by providing novel evidence on how a migrant TMT affects corporate decision-making.
Keywords: innovation; migrants; real earnings management; risk-taking; top management team